Where the minimum wage bites workers. Factor substitutability and innovativeness at the workplace - Kai-Uwe Müller; Alexandra Fedorets (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Exploiting variation in the bite of the German minimum wage we estimate its impact on employment. We break down effect heterogeneity for different degrees of labor substitutability based on admin data on job content and survey data on the workplace. While the average effect is insignificant, interacting treatment with substitutability, we get significantly effects on the probability of remaining employed and the transition to unemployment for employees more easily substitutable by capital.
Keywords: H22; J38; H55; J20; 330